(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Advanced Life Support (ALS) is a critical component of emergency medical care, involving specialized interventions to stabilize patients facing life-threatening conditions. This article examines the essential roles of paramedics and nurses in delivering ALS, emphasizing their collaborative efforts to improve patient outcomes. Paramedics perform primary assessments, airway management, intravenous access, and cardiac monitoring, while nurses contribute within hospital settings, administering medications, monitoring vital signs, and ensuring seamless transitions of care. Effective teamwork and communication between paramedics and nurses are paramount in ALS scenarios, supported by advancements in technology and ongoing research initiatives.